2017
DOI: 10.1007/s10493-017-0176-0
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Euseius concordis (Mesostigmata: Phytoseiidae) to pesticides used in citrus production systems

Abstract: Euseius concordis (Chant) is an important predatory mite found in citrus orchards. The toxicity of 19 pesticides used in citrus orchards on biological and population parameters of this mite was assessed. Our results indicated that formetanate hydrochloride, dimethoate and phosmet were highly harmful (100% mortality) to E. concordis. Carbosulfan, diflubenzuron, fenpropathrin, gamma-cyhalothrin, imidacloprid, lambda-cyhalothrin, lambda-cyhalothrin + thiamethoxam, mineral and vegetable oils, spinosad and thiameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Even 31 days after spraying, these pesticides continue to exert a highly harmful residual activity on P. longipes adults. Previous studies consistently reported similar harmful effects and persistence of pyrethroids and organophosphates on various natural enemies, including phytoseiid species (Abou-Awad and El-Banhawy 1985; Villanueva and Walgenbach 2005;Broufas 2008;Bostanian et al 2010;Hamby et al 2013;Beers and Schmidt 2014;Franco et al 2017;Schmidt-Jeffris et al 2021). These results suggest that organophosphates and pyrethroids are not compatible with P. longipes.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Even 31 days after spraying, these pesticides continue to exert a highly harmful residual activity on P. longipes adults. Previous studies consistently reported similar harmful effects and persistence of pyrethroids and organophosphates on various natural enemies, including phytoseiid species (Abou-Awad and El-Banhawy 1985; Villanueva and Walgenbach 2005;Broufas 2008;Bostanian et al 2010;Hamby et al 2013;Beers and Schmidt 2014;Franco et al 2017;Schmidt-Jeffris et al 2021). These results suggest that organophosphates and pyrethroids are not compatible with P. longipes.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, we also observed that pesticides highly harmful to P. longipes through topical exposure in laboratory conditions are not necessarily persistent under screen-house conditions. These findings highlight the importance of assessing non-target effects on each predator life stage and exposure route Table 5 (continued) (Duso et al 2008;Biondi et al 2013;Put et al 2016;Fernández et al 2017;Franco et al 2017;Bergeron and Schmidt-Jeffris 2020;Döker and Kazak 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It allows us to fight pests on a large number of agricultural plants depending on the regulation of the country in which it is used. These plants include apple, almond, apricot, banana, bean, cabbage, carrot, citrus, cotton, cucumber, grape-wine, mango, melon, olive, papaya, pear, pepper, soybean, strawberry, tomato, watermelon, and zucchini [12][13][14][15][16][17][18]. The study of the behavior of pyriproxyfen for a given crop in the growing conditions of a specific area is compulsory to estimate whether the established pre-harvest time ensures that the residue levels are below the maximum residue level (MRL) that is the highest concentration of pesticide that is legally tolerated in or on food when it is applied under good agricultural practices.…”
Section: Introductionmentioning
confidence: 99%